2021
DOI: 10.3390/plants10030518
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacterial Blight Resistance Loci in Rice (Oryza sativa L.) against Diverse Xoo Thai Strains by Genome-Wide Association Study

Abstract: Bacterial leaf blight (BLB) is a serious disease affecting global rice agriculture caused by Xanthomonas oryzae pv. oryzae (Xoo). Most resistant rice lines are dependent on single genes that are vulnerable to resistance breakdown caused by pathogen mutation. Here we describe a genome-wide association study of 222 predominantly Thai rice accessions assayed by phenotypic screening against 20 Xoo isolates. Loci corresponding to BLB resistance were detected using >142,000 SNPs. We identified 147 genes according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
1
9
1
Order By: Relevance
“…Scores 0–2 were considered resistant (R), 3 as moderately resistant (MR), and 4-5 as susceptible (S). # Average lesion length <5 cm is resistant, >5-10 cm is moderately resistant, >10-15 cm is moderately susceptible, and >15 cm susceptible ( Korinsak et al., 2021 ); Chr, Chromosome. Different alphabet of small letters denoted in superscript is defined as significantly different groups which authors have got from duncan's test to perform haplo-pheno test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores 0–2 were considered resistant (R), 3 as moderately resistant (MR), and 4-5 as susceptible (S). # Average lesion length <5 cm is resistant, >5-10 cm is moderately resistant, >10-15 cm is moderately susceptible, and >15 cm susceptible ( Korinsak et al., 2021 ); Chr, Chromosome. Different alphabet of small letters denoted in superscript is defined as significantly different groups which authors have got from duncan's test to perform haplo-pheno test.…”
Section: Resultsmentioning
confidence: 99%
“…The mean of two fully expanded leaf from three replicate plants for each accession were taken for determining the reaction type. A plant was classified as resistant if the average lesion length was shorter than 5 cm, moderately resistant if the lesion was >5-10 cm, moderately susceptible if the lesion was >10-15 cm, and susceptible if the lesion was >15 cm ( Korinsak et al., 2021 )…”
Section: Methodsmentioning
confidence: 99%
“…Our results showed that the LD levelness was the highest at r 2 = 0.24, gradually beginning to decrease at r 2 = 0.12 when the physical distance increased to 7 kb, and low ( r 2 = 0.035) when the physical distance increased to 50 kb. The result was lower than self-pollination plants Prunus avium [ 44 ] and rice [ 20 ]. This may be due to the self-incompatibility of tea plants [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A GWAS analysis of 236 diverse rice accessions revealed 12 QTLs, of which two QTLs showed broad-spectrum resistance to Xoc [ 91 ]. Recently, 147 SNP associated with Xoo resistance were identified in 222 predominantly Thai rice accessions; however, the significantly associated SNP only occurred across a maximum of five Xoo isolates [ 92 ]. In rice, most resistance QTLs are conditioned to different populations and different QTL mapping analyses, which makes it difficult to handpick suitable QTL candidates for breeding programs with multiple resistances.…”
Section: Identified Rice Broad-spectrum Disease Resistance Genes In Past 10 Yearsmentioning
confidence: 99%